2011
DOI: 10.1093/nar/gkr793
|View full text |Cite
|
Sign up to set email alerts
|

The CHR promoter element controls cell cycle-dependent gene transcription and binds the DREAM and MMB complexes

Abstract: Cell cycle-dependent gene expression is often controlled on the transcriptional level. Genes like cyclin B, CDC2 and CDC25C are regulated by cell cycle-dependent element (CDE) and cell cycle genes homology region (CHR) promoter elements mainly through repression in G0/G1. It had been suggested that E2F4 binding to CDE sites is central to transcriptional regulation. However, some promoters are only controlled by a CHR. We identify the DREAM complex binding to the CHR of mouse and human cyclin B2 promoters in G0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

12
201
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 97 publications
(213 citation statements)
references
References 55 publications
(95 reference statements)
12
201
0
Order By: Relevance
“…Chromatin immunoprecipitation (ChIP) has located DREAM proteins at a majority of E2F and cell cycle homology region (CHR) promoters in human cells, and gene expression analysis has implicated DREAM as a repressor of cell cycle genes (Litovchick et al 2007;Schmit et al 2007;Muller et al 2012). The mechanism of how DREAM regulates transcription has not been elucidated, but it is clear that its central components scaffold a number of key cell cycle transcription factors, including E2F4/ 5, B-Myb, FoxM1, and the Rb tumor suppressor family paralogs p107 and p130 (Korenjak et al 2004;Lewis et al 2004;Litovchick et al 2007;Schmit et al 2007;Sadasivam et al 2012).…”
mentioning
confidence: 99%
“…Chromatin immunoprecipitation (ChIP) has located DREAM proteins at a majority of E2F and cell cycle homology region (CHR) promoters in human cells, and gene expression analysis has implicated DREAM as a repressor of cell cycle genes (Litovchick et al 2007;Schmit et al 2007;Muller et al 2012). The mechanism of how DREAM regulates transcription has not been elucidated, but it is clear that its central components scaffold a number of key cell cycle transcription factors, including E2F4/ 5, B-Myb, FoxM1, and the Rb tumor suppressor family paralogs p107 and p130 (Korenjak et al 2004;Lewis et al 2004;Litovchick et al 2007;Schmit et al 2007;Sadasivam et al 2012).…”
mentioning
confidence: 99%
“…The CHR is typically located at or close to the transcriptional start site. Recently, it was shown that the CHR element is bound by the DREAM and MMB transcriptional regulatory complexes, and these complexes play a role in controlling cell cycledependent transcription of genes expressed at the G 2 -M border (10). The DREAM and MMB complexes are functionally interrelated, and both contain the MuvB core complex, which includes LIN9, LIN37, LIN52, LIN54, and RBBP4 in addition to specific additional subunits in each case (11,12).…”
mentioning
confidence: 99%
“…The oncoprotein B-Myb is a key regulator in the switch between transcriptional repression and activation of a large number of genes including PLK1, Aurora A, Cyclin A and Cyclin B1/2 during cell cycle progression through the G2 phase [9][10][11] . B-Myb is part of the transcriptionally activating Myb-MuvB complex, which binds to the CHR promoter elements thereby replacing the DREAM repressor complex 9 .…”
mentioning
confidence: 99%
“…B-Myb is part of the transcriptionally activating Myb-MuvB complex, which binds to the CHR promoter elements thereby replacing the DREAM repressor complex 9 . Interestingly, binding of B-Myb was observed in promoters of many genes controlling the transition from G2 to M phase, and contact to promoter regions appeared to depend on the CHR element, but not on Myb-binding sites 11 .…”
mentioning
confidence: 99%
See 1 more Smart Citation